Homosexuality, transsexuality, psychoanalysis and traditional Judaism - Slomowitz, Alan; Feit, Alison (Psychoanalysis in a new key book series, 2019)
Sexual identity and psychoanalysis in traditional Judaism -- Preface: moving the conversation along by / Jack Drescher, MD -- Does God make referrals : Orthodox Judaism and homosexuality / Alan Slomowitz, Ph.D. and Alison Feit, Ph.D -- Collateral damage : clinical and theoretical material of the unrecognized psychic and social damage caused by not recognizing and accepting LGBTQ members into the full context of the Orthodox community / Mark Blechner, Ph.D -- Discussion of "does god make referrals : Orthodox Judaism and homosexuality" / Ronnie Lesser, Ph.D -- Response to does god make referrals and Drs. Blechner and Lesser papers / Rabbi Mark Dratch, LMSW -- Pastoral counselling and LGBTQ Orthodox Jews / Michelle Friedman, MD -- Gay Jewish men in the Orthodox Jewish community : striving for selfhood / Jeremy Novich, Ph.D -- The parents are our future / Miryam Kabakov, LMSW -- Envisioning an orthodox gay wedding / Rabbi Steven Greenberg -- Women known for these acts / Elaine Chapnik, JD -- Gender identity and psychoanalysis in traditional Judaism -- Fausto-sterling : the dynamic development of gender variability / Anne Fausto-Sterling, Ph.D -- Transgender experiences and issues in Orthodox Jewish community : summary of findings / Oriol Poveda, Ph.D -- Genocide, transsexuality, the limits of coherence, and the radiance of the universe / Ben Baader, Ph.D -- Border crossings : commentary on Ben Baader's paper / Seth Aronson, Psy.D -- Knowing the soul of the stranger / Joy Ladin, Ph.D -- Rabbinic and halachic discourse on sex change surgery and gender definition / Hillel Gray, Ph.D -- Orthodox Judaism and its transgender members / Rabbi Hayim Shaffner, LCSW.